Community‐deliverable exercise and depression in adults with arthritis: Confirmatory evidence of a meta‐analysis using the IVhet model. Issue 1 (18th December 2017) - Kelley, George A.; Kelley, Kristi S.
Abstract: Objective: Using the traditional random‐effects model, a recently reported standardized effect size (g) reduction of −0.42 (95% CI, −0.58 to −0.27) was observed in depressive symptoms as a result of community‐deliverable exercise in adults with arthritis and other rheumatic diseases. However, a recently proposed alternative model (IVhet) has been shown to have superior coverage probability to the random‐effects model. The purpose of this brief report was to compare these previous random‐effects results with the IVhet model. Methods: Based on a previous meta‐analysis of 35 g's representing 2449 participants, results for depressive symptoms were pooled using the IVhet model. Influence analysis, number needed‐to‐treat, percentile improvement, and gross estimates of the number of inactive adults with arthritis who could benefit from exercise were also calculated. Results: The IVhet model yielded statistically significant reductions in depressive symptoms (g = −0.30, 95% CI, −0.49 to −0.11), a difference that was −0.12 (28.7%) smaller than the random‐effects model. With each study deleted from the model once, results remained statistically significant, ranging from −0.28 to −0.34. The percentile improvement, number needed‐to‐treat, and estimated number of people with arthritis in the United States who could improve their depressive symptoms by participating in a regular exercise program were, respectively, 11.8% (95% CI, 4.5% to 18.8%), 8 (95% CI, 5 to 23), and 2.7 million (95% CI, 1.0 to 4.4 million). Conclusions: These findings provide more conservative and accurate evidence that community‐deliverable exercise improves depressive symptoms in adults with arthritis and other rheumatic diseases. Future meta‐analyses may want to consider using the IVhet versus traditional random‐effects model.